Seroprevalence of Neospora caninum-specific antibodies in German breeding bitches - Villagra-Blanco, Rodolfo; Angelova, Lora; Conze, Theresa; Schares, Gereon; Bärwald, Andrea; Taubert, Anja; Hermosilla, Carlos; Wehrend, Axel; Justus Liebig University Giessen (My University, 2018)
Background: Neospora caninum is an intracellular obligate apicomplexan parasite responsible for multisystemic lesions in dogs. Being definitive hosts and reservoirs, dogs excrete environmentally resistant oocysts. Breeding bitches represent a susceptible dog group and infected bitches may spread this parasite through transplacental transmission.Results: A total of 218 serum samples of German breeding bitches were collected to determine the presence of N. caninum. Antibodies were detected in 16 (7.33%) bitches using a commercial indirect enzyme-linked immunosorbent assay (ELISA). Immunoblotting analysis confirmed all seropositive samples detected by ELISA, proving that the animals were infected with N. caninum. The owners were interviewed regarding breed, age, environment, type, vaccine status, feeding habits and the presence of reproductive disorders. Seropositive animals were between the ages of two to seven years; three of them were kept in kennels while the others were household dogs, one of which was additionally a hunting dog. Owners of four seropositive bitches reported one gestation, while multiple pregnancies had been recorded for the other twelve bitches. Fourteen bitches were regularly vaccinated and six were fed with fresh raw meat.Conclusions: Although the results confirmed a low incidence of N. caninum seropositive German breeding bitches, further epidemiological and surveillance studies are required to complement our findings regarding the current situation of neosporosis in this specific canine population of Germany.
Keywords: Neospora caninum; Reproduction; Breeding bitches; Germany; ddc:630